Different doses of theacrine do not improve 4 km cycling time trial performance - Vieira-Cavalcante, V.; Schamne, J. C.; Gonçalves, F.; Bertuzzi, R.; Pierucci, A. P. T. R.; Boari, D.; Lima-Silva, A. E.; Silva, R. G. (Applied Physiology, Nutrition, and Metabolism, 2025)
The aim of the present study was to test the effects of different doses of anhydrous theacrine (3 and 6 mg·kg-1 of body mass) on 4 km cycling time trial performance. Nineteen (11 men and 8 women) cyclists (30.8 ± 10.0 years, 71.7 ± 11.8 kg, 170.1 ± 9.0 cm, and 17.0 ± 6.2% of body fat) completed three 4 km cycling time trials after ingesting either placebo, or 3 or 6 mg·kg-1 of body mass of theacrine. No significant differences (p < 0.05) were observed in time to cover the 4 km cycling time trial between the placebo, 3 mg·kg-1 of theacrine, and 6 mg·kg-1 of theacrine conditions. However, the intake of theacrine at the dose of 6 mg·kg-1 increased resting systolic and diastolic blood pressure (p < 0.05). Some side effects, such as gastrointestinal discomfort, perception of tachycardia, dizziness, headache, head pressure, hand tremor, and lack of disposition were reported after the ingestion of either 3 or 6 mg·kg-1 of body mass of theacrine. In conclusion, theacrine supplementation does not improve endurance performance and provokes side effects that might restrict its use as a supplement.